How New Product Development Affect Business Resilience of MSMEs in The Tourism and Creative Industry in Magelang - Ibrahim, Muhamad Wahid; Murniningsih, Rochiyati; Ra’uuf, Syuhada Abdi; Ilma Ratnawati (Jurnal Manajemen Bisnis, 2025)
This study aims to investigates the influence of Open Innovation (OI), Customer-Centricity (CC), and Competitive Orientation (CO) on organizational resilience among creative industry and tourism-related MSMEs in Magelang, Indonesia. Using a quantitative approach with survey data from 161 respondents, the analysis, conducted via multiple linear regression, shows that OI and CO significantly enhance resilience, while CC does not have a statistically significant effect. Grounded in Organizational Resilience Theory, the study emphasizes that resilience is strategically developed through innovation and market adaptability. The findings contribute to resilience theory and provide practical insights for strengthening resilience in the creative and tourism sectors.